Variability in natural populations of Sinorhizobium meliloti in Morocco - Thami Alami I.; Elboutahiri N.; Udupa S.M. (The contributions of grasslands to the conservation of Mediterranean biodiversity, 2010)
In Morocco, alfalfa (Medicago sativa L.) is being grown in harsh environments (such as mountains and oasis) and is frequently subjected to abiotic stresses such as salinity, drought and high temperature. Both alfalfa and its nitrogen fixing symbiotic bacteria Sinorhizobium meliloti are affected by these abiotic stresses. Improvements in biological nitrogen fixation could be achieved through selection of tolerant strains of S. meliloti to these abiotic stresses and inoculating them to the crop and also growing tolerant cultivars. This study examines phenotypic diversity for tolerance to drought, extremes of temperature and soil pH, soil salinity and heavy metals and genotypic diversity at Repetitive Extragenic Pallindromic DNA regions of 157 Sinorhizobium isolates, sampled from marginal soils of arid and semi-arid regions of Morocco. The results revealed high degree of phenotypic and genotypic diversity in Sinorhizobium populations. Further more, the isolates which showed tolerance to salinity stress also showed tolerance to water stress, indicating direct relationships between these two physiological pathways. High salt and water stress tolerant strains were isolated and tested for their ability to biological nitrogen fixation. Some of the isolated tolerant strains were also efficient nitrogen fixers, under water and salt stress conditions. The Analysis of Molecular Variance revealed that largest proportion of significant genetic variation was distributed within regions than among regions.
13. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM International Network for the Research and Development of Pasture and Forage Crops, 2010/04/07-10, Alicante (Spain)